2022
DOI: 10.3389/fpsyt.2022.976601
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the impact of COVID-19 on the game addiction of children and adolescents

Abstract: BackgroundDuring the COVID-19 pandemic, it is reported that children and adolescents who are socially isolated experience high levels of stress and various mental health problems. At present, little research has been done to collect previous studies that focused on game addiction in children and adolescents during the COVID-19 pandemic. In this research, we aimed to investigate the prevalence of gaming disorder during COVID-19 in children and adolescents and the various factors experienced by children and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 65 publications
1
13
0
3
Order By: Relevance
“…This study collected data only a few months after the COVID-19 lockdown was lifted in Saudi Arabia, while some restrictive measures were still in place [29]. The pandemic impacted the gaming behaviors of children, adolescents, and young adults, and emerging literature reported an increased prevalence of IGD after the lockdown [30]. A study by Alsaad et al found that 69.5% of the children and adolescents in their sample reported increased gaming behavior due to pandemic related-stress [31].…”
Section: Discussionmentioning
confidence: 99%
“…This study collected data only a few months after the COVID-19 lockdown was lifted in Saudi Arabia, while some restrictive measures were still in place [29]. The pandemic impacted the gaming behaviors of children, adolescents, and young adults, and emerging literature reported an increased prevalence of IGD after the lockdown [30]. A study by Alsaad et al found that 69.5% of the children and adolescents in their sample reported increased gaming behavior due to pandemic related-stress [31].…”
Section: Discussionmentioning
confidence: 99%
“…Applications to child and adolescent psychiatry clinics with digital addiction complaints are increasing day by day [1]. The COVID-19 pandemic has caused this increase to become evident [4,5,8]. Digital game disorders are more common in people with high levels of depression, anxiety, and stress [8].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has caused this increase to become evident [4,5,8]. Digital game disorders are more common in people with high levels of depression, anxiety, and stress [8]. For this reason, people with digital addiction may have an underlying psychiatric illness.…”
Section: Discussionmentioning
confidence: 99%
“…Young adults who show a serious level of excessive gaming and health-related risk behaviors are being impacted during the pandemic (Han et al, 2022 ; She et al, 2021 ). However, studies on which health-related risk behaviors are impacted by the severity of game usage are still lacking.…”
Section: The Impact Of Gaming On Youthmentioning
confidence: 99%